La responsabilidad penal de la persona jurídica como mecanismo necesario en el ámbito penal para la protección del ambiente en el departamento de la libertad - Vejarano Vargas, Miguel Ángel (2016)
The environmental impact of business activity, is a serious problem that currently faces the country, both industry and trade and mining, to mention a few, are activities that are generating negative impacts to the environment, which are aggravated by the absence of effective legal mechanisms to help prevent these effects, so in the present investigation, it addresses the need for the aplicación of criminal liability of the legal person as a necessary mechanism, in the criminal field, to protect the environment of business conduct that generate a serious affectation to the environment in the departament of La Libertad